Probe: Masha Gessen on Authoritarianism, and Walter J. Ong’s Thought - Farrell, Thomas J. (New Explorations, 2024)
First, I highlight Masha Gessen’s op-ed “The Seeds of This Political Disaster Were Sown Decades Ago” (dated July 20, 2024) in the New York Times. Next, I highlight certain points from the work of the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) of Saint Louis University. I style my short essay a “Probe” because it is fundamentally exploratory and tentative.